2020
DOI: 10.1101/2020.01.14.906115
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Symmetry breaking andde-novoaxis formation inhydraspheroids: the microtubule cytoskeleton as a pivotal element

Abstract: The establishment of polarity in cells and tissues is one of the first steps in multicellular development. The 'eternal embryo' hydra can completely regenerate from a disorganised cell cluster or a small fragment of tissue of about 10, 000 cells. During regeneration, the cells first form a hollow cell spheroid, which then undergoes de-novo symmetry breaking to irreversibly polarise. Here, we address the symmetry-related shape changes. Prior to axis establishment, the spherical aggregates of regenerating cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 83 publications
0
2
1
Order By: Relevance
“…1b ). This is clearly different from previous studies, where specimens were fixed in agar gels or confined in hanging liquid droplets (18), which affects the whole deformation dynamics of the system. To define the biomechanical symmetry breaking geometrically during Hydra regeneration, we Fourier transformed the radial distance between the contour and the center of mass r ( θ, t ) of the specimens during the whole regeneration process that took about 90 h (Fig.…”
Section: Resultscontrasting
confidence: 93%
See 1 more Smart Citation
“…1b ). This is clearly different from previous studies, where specimens were fixed in agar gels or confined in hanging liquid droplets (18), which affects the whole deformation dynamics of the system. To define the biomechanical symmetry breaking geometrically during Hydra regeneration, we Fourier transformed the radial distance between the contour and the center of mass r ( θ, t ) of the specimens during the whole regeneration process that took about 90 h (Fig.…”
Section: Resultscontrasting
confidence: 93%
“…1a right) (16, 17) plays a key role in Hydra regeneration. Ott and co-workers monitored the deformation of regenerates embedded in agar gels (16) or in droplets (18), and proposed that the morphological symmetry breaking occurs at the time point when the frequency of periodic deformation becomes higher. Keren and co-workers monitored the orientation of actin fibers in regenerates taken from different body parts, and suggested that the actin fiber orientation inherited from the parent animal determines the body axis after regeneration (19).…”
Section: Introductionmentioning
confidence: 99%
“…The most fundamental property of gum Arabic its water solubility and high viscosity but does not thicken the product. It has approved by FDA as pharmaceutical products that use in a wide variety of applications mainly as tablet binder, film forming agent, emulsifier, and suspending agent [11]. Gum Arabic is a multifunctional hydrocolloid with a highly branched arabinogalactan protein complex; it is often described as globular in shape.…”
Section: Introductionmentioning
confidence: 99%